Volume 7: 31st International Conference on Design Theory and Methodology 2019
DOI: 10.1115/detc2019-98125
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Mind-Mapping: A Study of Patterns, Strategies, and Evolution of Maps Created by Peer-Pairs

Abstract: We present a study on collaborative mind-mapping to understand how peers collaborate in pairs to create mind-maps, how the maps evolve over time, and how collaboration changes between the peer-pair across multiple maps. Mind-mapping is an important tool that is studied and taught in design practice and research respectively. While widely used as a brainstorming technique, the collaborative aspects of mind-mapping are little understood in comparison to other ideation methods such as concept sketching etc. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Digital mind maps include both digital pictorial and text information and allow ideas to be externalized as a structured neural network including textual and visual images of concepts originating from a central idea and to be disseminated as branches of related information [5,6]. In the literature, past research has found that digital mind mapping can be used to enhance both individual and collaborative learning [7].…”
Section: Digital Mind Mapmentioning
confidence: 99%
“…Digital mind maps include both digital pictorial and text information and allow ideas to be externalized as a structured neural network including textual and visual images of concepts originating from a central idea and to be disseminated as branches of related information [5,6]. In the literature, past research has found that digital mind mapping can be used to enhance both individual and collaborative learning [7].…”
Section: Digital Mind Mapmentioning
confidence: 99%
“…CMM facilitates the visualization of the connection between the main theme and problem branches (Hakim et al, 2020). In addition, CMM permits limitless idea exploration prior to problem resolution (Chen et al, 2019;Hung et al, 2014;Y.-T. Lin et al, 2016). This study reveals that the RICOSRE and RICOSRE-CMM models effectively enhance students' problem-solving skills.…”
Section: The Combination Of Ricosre and Collaborative Mind Mapping In...mentioning
confidence: 75%
“…The learning process that incorporates digital technology can also enhance students' diverse skills and knowledge (Al-Abdullatif & Gameil, 2021;Rosba et al, 2021). Applications that can be used to make CMM include: Coggle (Kamrozzaman et al, 2018;Papushina et al, 2017), iMindMap (Wan Jusoh & Ahmad, 2016), GroupMind (Shih et al, 2009), Mindmeister, Popplet and, Mindomo (Arajuo & Gadanidis, 2020;Chen et al, 2019) as well as web-based applications such as www.prosseson.com (Zheng et al, 2020). The CMM platform used in this research is Miro.…”
Section: Interventionmentioning
confidence: 99%
“…Therefore, it can be assumed that the integration between collaborative learning and the mind-mapping technique might be effective to enhance students' engagement. Chen et al (2019) discovered enhanced comfort and engagement among mind-mapping collaborators, and this collaboration allowed participants to explore more ideas. According to Chen et al (2019), more in-depth research is needed to uncover the process involved in collaborative mind-mapping, as it has been rarely mentioned by researchers in the past.…”
Section: Introductionmentioning
confidence: 97%
“…Chen et al (2019) discovered enhanced comfort and engagement among mind-mapping collaborators, and this collaboration allowed participants to explore more ideas. According to Chen et al (2019), more in-depth research is needed to uncover the process involved in collaborative mind-mapping, as it has been rarely mentioned by researchers in the past. To close this gap, we intended to describe students' engagement in a digital mind mapping-supported collaborative classroom.…”
Section: Introductionmentioning
confidence: 97%